Mindfulness-Based Cognitive Therapy Group Counseling Training for Counselors: Efforts to Improve Emotional Regulation - Wibowo, Mungin Eddy; Sunawan, Sunawan; Mulawarman, Mulawarman; Febrianti, Thrisia; Susilawati, Susilawati; Fuadina, Nabila; Yani, Indri (International Journal of Public Devotion, 2023)
In the current era, it is very important to pay attention to emotional regulation, where in the current era of technological advances, emotional regulation is at a low level, especially in junior high school students. Guidance and counseling services are services that are expected to improve students' emotional regulation with various forms of services, while group counseling services using the mindfulness based therapy method are still rarely carried out in schools. Therefore, the service team intends to help by providing group counseling training using the mindfulness based therapy method to increase the skills of guidance and counseling teachers, especially in overcoming students' low emotional regulation. There were 40 guidance and counseling teachers who took part in this training and there were only 11 guidance and counseling teachers who were able to show that this training was successful, of which 11 teachers had training results in the very high category. Furthermore, there are 2 in the high category, 26 in the moderate category and 1 low.